Vitamin Status as a Determinant of Serum Homocysteine Concentration in Type 2 Diabetic Retinopathy. (10th June 2014) - Fotiou, Pandelis; Raptis, Athanasios; Apergis, George; Dimitriadis, George; Vergados, Ioannis; Theodossiadis, Panagiotis
Abstract : We investigated the association of serum homocysteine levels and vitamin status with type 2 diabetic retinopathy. This study included 65 patients with and 75 patients without diabetic retinopathy. Patients with diabetic retinopathy had significantly higher serum homocysteine levels P < 0.001, higher prevalence of hyperhomocysteinemia P < 0.001, lower serum folic acid P < 0.001, and vitamin B12 (P = 0.014 ) levels than those without diabetic retinopathy. Regression analysis revealed that homocysteine was an independent risk factor for diabetic retinopathy and there was a threshold in its serum level (13.7  μ mol/L), above which the risk of diabetic retinopathy greatly increases (O R = 1.66, P = 0.001 ). Folic acid was associated with decreased odds for diabetic retinopathy (O R = 0.73, P < 0.001 ). There was a threshold in serum vitamin B12 level (248.4 pg/mL), below which serum homocysteine concentration significantly increases with decreasing serum vitamin B12 (P = 0.003 ). Our findings suggest that hyperhomocysteinemia is an independent risk factor for the development and progression of diabetic retinopathy. Decreased serum levels of folic acid and vitamin B12, through raising serum homocysteine concentrations, may also affect the diabetic retinopathy risk.